The influence of organizational learning and organizational innovativeness and the mediating effect of leadership styles / Shahri Abu Seman - Abu Seman, Shahri (2020)
Private Higher Educational Institutions (PHEIs) which equipped with organizational learning can improve academic managers’ innovativeness, and produce graduates with innovative capabilities. This study was conducted to determine the influence of organizational learning on organizational innovativeness and investigating the mediating effect of leadership style in private higher educations in Malaysia. Transformational leadership, transactional leadership, and laissez-faire leadership style were measured as mediating variables that influenced the relationship between organizational learning and organizational innovativeness. This quantitative survey research involved 220 academic managers from four different statuses of private higher education institutions as the research respondents and data were collected using questionnaires and analyzed using computer software of Statistical packages for Social Science (SPSS) version 24. The finding of the study indicated that there was a strong relationship between organizational learning and organizational innovativeness. The finding also confirms the importance and major effect of leadership style as mediators on the relationship between organizational learning and innovativeness. This study made a significant contribution to the organizational learning-organizational innovativeness literature by developing an integrative model that combines organizational learning, leadership style, and organizational innovativeness. The paper helps the policymakers to see the connection between the learning development situation of Private Higher Education Institutions (PHEIs) and innovation practice in Malaysia and at the same time, it will promote international understanding of the PHEIs in Malaysia. These research findings were expected to improve an application of innovation by PHEIs to face national challenges, improve an education system, and make it accessible, affordable and equitable to everybody. This study and findings would serve as a resourceful reference in connecting the quality of education with innovation levels.